Answers:
- a)
- b)
Each answer has 7 as the base and a fraction as an exponent.
==========================================================
Step-by-step explanation:
One useful rule here is that
. The fraction m/n is the exponent for the base x. Note how the index of the root (n) becomes the denominator of the fraction m/n. So for example if we had n = 3, then we'd be dealing with a cube root.
For part a), we have x = 7, m = 1 and n = 5 to get
-----------------
Part b) is the same idea
We would find that
Then apply the reciprocal to both sides. This is the same as raising both sides to the exponent -1
You could also use the rule that x^(-y) = 1/(x^y) when dealing with negative exponents.
In the second to last step shown above, I used the rule (x^y)^z = x^(y*z) on the right hand side.